2014
DOI: 10.1155/2014/121838
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Formalin Fixation on Surgical Margins in Breast Cancer Surgical Specimen

Abstract: Margin analysis in breast surgery is an important predictor of local recurrence and can have vital impact on the postoperative treatment planning. Objective. The aim was to assess the mean reduction in the closest tumor-free surgical margin in millimeters of breast cancer specimens following formalin fixation. Materials and Methods. We conducted a cross-sectional study at the Aga Khan University Hospital from March 30, 2010 to January 20, 2011. One hundred consecutive breast tumour surgical specimens which had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Krekel et al found no change of tumourfree margins or tumour shrinkage of breast cancer specimen following formalin fixation [31]. However, authors have shown that shrinkage affects surrounding tissue and influences tumour margins, rather than tumour size itself [32,33]. Therefore, underestimation of real tumour size by histopathology due to formalin fixation may be discussed in case the tumour diffusely infiltrates surrounding tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Krekel et al found no change of tumourfree margins or tumour shrinkage of breast cancer specimen following formalin fixation [31]. However, authors have shown that shrinkage affects surrounding tissue and influences tumour margins, rather than tumour size itself [32,33]. Therefore, underestimation of real tumour size by histopathology due to formalin fixation may be discussed in case the tumour diffusely infiltrates surrounding tissue.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that formalin fixation caused slight muscle expansion and shrinkage of fatty tissue, which could affect the accuracy of tumor-free margin measurements. Significant shrinkage of tumorfree surgical margin after formalin fixation was noted in breast cancer specimens with a mean reduction of 10% in size, 14 while in renal tumors an overall shrinkage of 11.4% between fresh and histological specimens was observed. 18 To date, there have been 3 studies investigating the effect of formalin fixation on colorectal cancer specimens.…”
Section: Discussionmentioning
confidence: 92%
“…Several other studies have showed that often residual cancer is not found on final pathology after re-excision for a positive margin [7-9, 14, 15]. In other words, a margin could be incorrectly considered positive after handling of the specimen for histopathological analysis, since the pathologist might misunderstand its interpretation due to specimen shrinkage [16,17]. Another point to be considered is the type of margin involvement.…”
Section: Discussionmentioning
confidence: 99%